The social wasp community (Hymenoptera, Vespidae) in an area of Atlantic Forest, Ubatuba, Brazil - Togni, Olga Coutinho [UNESP]; Locher, Gabriela de Almeida [UNESP]; Giannotti, Edilberto [UNESP]; Silveira, Orlando Tobias (Pensoft Publishers, 2014)
The Brazilian Atlantic Forest is of great relevance to biological conservation, and is among the areas in South America with the highest levels of diversity and endemism. The aim of this study was to survey the social wasp species in the subfamily Polistinae in Ubatuba, São Paulo state, in southwestern Brazil. Collecting work was conducted from May 2007 to May 2008 using attractive PET bottle traps and active searching. Twenty-one species belonging to eight genera were found, among which some may be considered rare in southeastern Brazil such as Mischocyttarus parallelogrammus and Polybia catillifex. The most abundant species were Agelaia angulata (64.31%), Agelaia nr. centralis (10.08%) and Angiopolybia pallens (8.49%). A correlation between species richness and relative humidity (r = 0.6435; p = 0.0176) was observed. Values of species richness were a little higher in the super humid (Sm = 11) than in the less humid (Sm = 9) season. This suggests that this season may have more favorable environmental conditions for a greater richness of species to found colonies. Despite not having a very high species richness compared with other surveys, the collected species in this study can be considered rare in southeastern Brazil, emphasizing the complexity of the Atlantic Forest biome and its relation to the diversity of wasps. © 2014 Check List and Authors.